A galactoarabinan-containing glycoprotein isolated from the fruits of Lycium barbarum reverses the tumor-associated macrophage phenotype - Wang, Bo; Lu, Bowen; Lv, Junqiang; Dong, Caixia; Bai, Changcai (Frontiers in Pharmacology, 2025)
Lycium barbarum fruits possess a well-established history of use in traditional Chinese medicine due to their potent immunomodulatory properties, extending to cancer immunity. In this study, a purified galactoarabinan-containing glycoprotein, designated LBNP-1, with an apparent molecular weight of 56.2 kDa, was isolated from the aqueous extract of L. barbarum fruits. Our findings revealed that LBNP-1 possesses a branched arabinan structure as its saccharide moiety. Bioactivity assays demonstrated that LBNP-1 polarized M2 macrophages towards the M1 phenotype. Furthermore, the LBNP-1-induced macrophage phenotypic shift was inhibited by a TLR4 antagonist. Western blot analysis indicated that LBNP-1 activated the NF-κB signaling pathway, thereby promoting polarization of tumor-associated macrophages (TAMs) towards the M1 phenotype. Moreover, conditioned medium derived from RAW264.7 cells pretreated with LBNP-1 exhibited anticancer effects against colorectal cancer (CRC) cells. Our research highlights the antitumor effect of LBNP-1 against CRC, mediated by reversing the TAM phenotype. LBNP-1 may represent a potential immunomodulator for the treatment of malignancies.